Hubungan Citra Tubuh (Body Image) dengan Status Gizi Remaja di Smart Fast Global Education - Hatussaadah, Siti Fati; Rosalina, Elvin (Universitas Baiturrahim, 2024)
Adolescent nutritional status can be influenced by various factors. One factor that can influence the nutritional status of adolescents is body image. Body image can occur due to perceptions that tend to assess body size as being larger than its actual size. This is what causes most teenagers to use various unhealthy methods to achieve their satisfaction. These actions often pose a danger to themselves, such as losing weight through unhealthy diets and reducing food portions excessively, which will affect their nutritional status. From a survey seen on Smart Fast Education Global, it was found that most teenagers tend to have a negative body image and wrong eating patterns. The aim of this research is to see the relationship between body image and nutritional status of adolescents at Smart Fast Global Education Jambi. This research is a quantitative descriptive study with a cross sectional design. Sampling used a total sampling technique of 38 people. The data taken is body image and nutritional status based on BMI/U. Data analysis used Chi-Square to test the relationship between body image and nutritional status. The results of this study showed that there was no significant relationship between body image and nutritional status, this was marked by a p value of 0.072 (> 0.05). Adolescents are advised to receive assistance in instilling a confident attitude towards their body shape and are given education regarding good food choices and correct eating arrangements to achieve normal nutritional status.